Nonlinear Dynamic Analysis of a Curved Sandwich Beam with a Time-Dependent Viscoelastic Core Using the Generalized Differential Quadrature Method (GDQM) - Serveren, Mehmet Mert; Demir, Ozgur; Arikoglu, Aytac (MDPI, 2024)
This paper focuses on the geometrically nonlinear dynamic analyses of a three-layered curved sandwich beam with isotropic face layers and a time-dependent viscoelastic core. The boundary conditions and equations of motion governing the forced vibration are derived by using Hamilton's principle. The first-order shear deformation theory is used to obtain kinematic relations. The spatial discretization of the equations is achieved using the generalized differential quadrature method (GDQM), and the Newmark-Beta algorithm is used to solve the time variation of the equations. The Newton-Raphson method is used to transform nonlinear equations into linear equations. The validation of the proposed model and the GDQM solution's reliability are provided via comparison with the results that already exist in the literature and finite element method (FEM) analyses using ANSYS. Then, a series of parametric studies are carried out for a curved sandwich beam with aluminum face layers and a time-dependent viscoelastic core. The resonance and cancellation phenomena for the nonlinear moving-load problem of curved sandwich beams with a time-dependent viscoelastic core are performed using the GDQM for the first time, to the best of the authors' knowledge.
Keywords: sandwich structures; geometrically nonlinear analysis; generalized differential quadrature method (GDQM); VIBRATION ANALYSIS; TRANSIENT ANALYSIS; PLATES; SHELLS; THICK; Science & Technology - Other Topics